An amplification-free colorimetric test for sensitive DNA detection based on the capturing of gold nanoparticle clusters. Issue 29 (16th July 2020) - Tatulli, Giuseppina; Pompa, Pier Paolo
Abstract : A colorimetric assay for sensitive DNA detection was developed, exploiting the target-induced capturing of multiple gold nanoparticle clusters onto the surface of magnetic microbeads. The visual test achieves a performance comparable to PCR. Abstract : PCR-free or amplification-free strategies for DNA detection provide an interesting alternative to classical molecular biology techniques, opening new possibilities for on-site diagnostics. In this framework, we present herein an amplification-free colorimetric test for DNA detection, based on the capture of multiple gold nanoparticle (AuNP) clusters onto the surface of magnetic microbeads, leading to an increase of the plasmonic signal and, thus, of the overall sensitivity. Noteworthy, the assay allows the detection of as low as 15 attomoles of target DNA by simple visual inspection. The AuNP-cluster capturing mechanism was investigated by UV-vis, SEM, TEM, and EDX analysis. In a case study of E. coli contamination, the colorimetric test achieves a performance comparable to the reference instrumental PCR technique, enabling the naked-eye detection of 7.5 × 10 2 CFU μL −1 .